Energy poverty and health: Micro-level evidence from Germany - Martin Buchner; Miriam Rehm (RWI - Leibniz-Institut für Wirtschaftsforschung, 2025)
This paper aims to understand the health effects of energy poverty in Germany using SOEP panel data from 2010 to 2020. Linear probability models and fixed effects ordered logit models reveal a consistently negative relationship of three expenditures based energy poverty indicators with general health. The association is stronger for the subjective energy poverty metric: members of households unable to keep the home comfortably warm due to financial reasons have an about 3.23 p.p. lower probability of being in at least satisfactory health. Investigating potential channels shows that mental health is consistently negatively linked to our energy poverty metrics, while physical health is weakly associated with energy poverty in Germany, with the exception of doctor visits. Finally, by instrumenting energy poverty with data on energy price indices and matching energy costs to the heating systems used by households, we show that living in a household that experiences a transition to energy poverty due to rising energy prices is also linked to a lower likelihood of being in good health. – – Dieses Papier untersucht die gesundheitlichen Auswirkungen von Energiearmut in Deutschland auf Basis von Paneldaten des Sozio-oekonomischen Panels (SOEP) für den Zeitraum 2010 bis 2020. Unter Anwendung von Linear-Probability-Modellen sowie Fixed-Effects-Ordered-Logit-Modellen zeigt sich ein robuster negativer Zusammenhang zwischen drei objektiven Indikatoren für Energiearmut und dem allgemeinen Gesundheitszustand. Besonders stark ausgeprägt ist dieser Zusammenhang bei einem subjektiven Indikator: Personen aus Haushalten, die ihre Wohnung aus finanziellen Gründen nicht angemessen warmhalten können, haben eine um 3,23 Prozentpunkte geringere Wahrscheinlichkeit, sich in (mindestens) zufriedenstellendem Gesundheitszustand zu befinden. Eine weiterführende Analyse möglicher Wirkungsmechanismen deutet darauf hin, dass insbesondere die psychische Gesundheit negativ mit Energiearmut assoziiert ist, während sich für die körperliche Gesundheit nur schwache negative Zusammenhänge zeigen.
Keywords: I10; I32; Q41; 330; Energy poverty; health; fixed effects ordered logit models; Germany